Anthropomorphic metaphor in the english terminological system of biotechnology - Сиротіна, Олена Олексіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
In the article the study results of one of the possible ways of term formation in the biotechnological sphere namely metaphorization and the study of the metaphors are presented. Metaphorical nominations preserve the systematicity embedded in the terminology in its construction and based on the classifications formed in this field, as well as bring their systematicity into the term system. The relevance of the study is due to the need to explain the cognitive basis of the anthropomorphic metaphor as one of the mechanisms for creating biotechnological terms in the English language.The main sources of metaphorical nominations within the field of biotechnology have been identified. In the studied term system, associative-terminal parts of the names of biotechnological processes and objects are recipient zones, and donor zones are other conceptual spheres that supply their own signs.The most productive is the HUMAN donor zone. The most effective way of creating terminological units in the biotechnological terminology based on anthropomorphic metaphorization is substantiated. The transfer of nominations from the biotechnology commonly used in the term sphere is based on similarity in form, function and analogies. The semantic groups of terms-metaphors formed on the basis of the cognitive transfer of lexemes concerning the structure of the human body, his mental states and moods, social life and mode of life, into the specialized field due to the external or functional similarity between the objects of the source field and the target field.